The Role of Technology in The Representation of The True People in Nano Riantiarno's Performance of The Demonstrator Play - Devitalisa M, Wulan; Munaris, Munaris; Widodo, Mulyanto; Sumarti, Sumarti; Samhati, Siti (UNDIKMA, 2024)
This research discusses the role of technology in the representation of the true people in Nano Riantiarno's play